ZOLTÁN GÁRDONYI SERVING ECCLESIASTICAL MUSIC - Éva PÉTER (Studia Universitatis Babeş-Bolyai. Musica)
Zoltán Gárdonyi is an ecclesiastical musician, musicologist, composer and professor, an outstanding personality of the 20th century European music. The paper hereby offers a glimpse into the outstanding ecclesiastical choral pieces Zoltán Gárdonyi composed in his lifetime.